Pengaru work life balance terhadap kinerja karyawaan melalui kepuasan kerja - Muhammad Ridi Afandi Agus Masrul (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
The purpose of this research is to examine and analyze the effect of work-life balance on employee performance if it is mediated by job satisfaction on employee objects at PT Febri Dharma Mandiri, whose address is Puri Surya Jaya Taman Nagoya E3/66 Sidoarjo, East Java. The population used is permanent employees in all parts of PT Febri Dharma Mandiri, totalling 35 people. Quantitative research is applied to the sample population, and the measuring tool used is PLS (Partial Least Square). The results showed that work-life balance has a positive effect on employee performance, life balance has a positive effect on job satisfaction, job satisfaction has a positive effect on employee performance, work-life balance and job satisfaction have a positive effect on employee performance. In addition, it is proven that satisfaction mediates work-life balance on employee performance. Companies must maintain and improve work-life balance and job satisfaction, thereby creating and influencing employee performance improvements.